“Who’s Texting?” – Playful Game Experiences for Learning to Cope with Online Risks - Susi, Tarja; Torstensson, Niklas (HCI in Games, 2019)
This paper describes the development and evaluation of the innovative computer game Hidden in the Park, for 8–10 year old children. It is a mixed media game that includes classic game elements and Augmented Reality technology. It is a non-profit game designed for a playful game experience. But, it is also a serious game intended to raise young childrens’ risk awareness in online interactions, to decrease the risk of becoming the subject of online sexual grooming. The game is intended to evoke thoughts and reflections related to players’ decisions and their consequences. Furthermore, the game is based on research on true online grooming processes, which provides the basis for some central game mechanics. Game evaluations were carried out with 70 children in school settings. The results show that the participants perceived the game as fun and engaging, but that it also raised questions and reactions, as intended. Hidden in the Park will be released during 2019 and it will be available for free download.